Shota Rustaveli : (Encyclopedic Research) - Elguja Khintibidze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
The review article represents all issues concerning Rustaveli's work. The main emphasis falls on the questions of ideal world view and the specificity of artistic style of the MPS. The article deals with the methodology issues of Rustaveli Studies as well.